The impossible arises : Oscar Reutersvärd and his contemporaries - Mortensen, Chris (Special publications of the Lilly Library, 2022)
"The Impossible Arises explores the life and work of Oscar Reutersvärd (1916-2002), founder of the Impossible Figures movement. The movement began in Stockholm in 1934 when eighteen-year-old Reutersvärd drew the first impossible triangle. Over the course of his life he would go on to draw around 4000 impossible figures and be honored by the Swedish government with an issue of stamps showing his work. Based on a large collection of Reutersvärd's art and correspondence held at the Lilly Library at Indiana University Bloomington, the lavishly illustrated Impossible Arises examines the evolution of Reutersvärd's impossible figures and how they influenced other modern artists in the later twentieth century. The Impossible Arises offers a detailed look at the philosophy guiding Reutersvärd's art and presents a rich array of stories from his eccentric personal life. It is an essential introduction to the life and career of one of the most fascinating artists of the twentieth century"--